Second primary colorectal cancer after the initial primary colorectal cancer - Yang, Lin (BMC Cancer, 2018)
BACKGROUND: Initial primary colorectal cancer (IPCRC) has a high risk of developing into second primary colorectal cancer (SPCRC). Right-sided colon cancer (RCC) and left-sided colon cancer (LCC) have different characteristics and are considered to be two different entities. However, the different risks for SPCRC in categorized tumor sites and SPCRC subcategorized sites have not been fully elucidated to date. We aimed to compare incidence and survival of IPCRC and SPCRC and characterize the risk factors of SPCRC while also comparing the different SPCRC characteristics. METHODS: We used the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) data to compute standardized incidence ratios (SIR) in order to estimate risk of SPCRC after IPCRC diagnosis. The most prominent risk factors for SPCRC were measured by multivariate regression analysis and the temporal trend of SPCRC incidence was assessed with Joinpoint regression. Survival of patients with SPCRC and IPCRC was compared by Kaplan-Meier analysis. RESULTS: Patients with IPCRC were 1.73 times more likely to develop SPCRC (SIR = 1.73, 95% CI 1.69–1.78). SPCRC incidence declined since the first 8 years of IPCRC diagnosis to baseline. We demonstrated poorer survival with SPCRC compared with IPCRC while second RCC resulted in better survival compared with second LCC. Black ethnicity, age range 70–79, and LCC were associated with the highest risk of developing SPCRC. CONCLUSION: The characteristic differences between second LCC and RCC were relatively narrow. Furthermore, in those with SPCRC, RCC had the best survival outcome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4823-6) contains supplementary material, which is available to authorized users.